MULTIKULTURALISME DALAM PENDIDIKAN ISLAM: STUDI TEMATIK AL-QUR’AN DAN HADITS - Muhammad Ali Murtadho; Ridho Dwi Putra; Gusti; Ali Imron; Mukmin Zainal Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article discusses the concept of multiculturalism in Islamic education through a thematic study of Quranic verses and Hadith related to diversity. This study aims to uncover the normative foundations of multicultural education in Islam and its relevance to the development of contemporary educational practices. The method used is library research with a thematic approach (maudh'i), namely collecting, classifying, and analyzing verses and Hadith related to the principles of equality, tolerance, justice, and respect for differences. The results of the study show that the Quran emphasizes diversity as a sunnatullah that must be accepted constructively, as reflected in the principle of equal human dignity (QS. Al-Hujurat: 13), the prohibition of discrimination and fanaticism ('ashabiyyah), and the command to treat everyone fairly. The Hadith of the Prophet also reinforces these values ​​through the Prophet's life example in building an inclusive Medina society. The research findings confirm that Islamic education has a strong theological foundation for developing multicultural education that respects cultural, religious, and ethnic plurality. Thus, internalizing multicultural values ​​in Islamic education is important to implement to form students who are moderate, tolerant, and have a global perspective.